Detection of specific IgG antibodies in blood donors and tick-borne encephalitis virus in ticks within a non-endemic area in southeast Norway. (March 2014) - Larsen, Astri Lervik; Kanestrøm, Anita; Bjørland, Marthe; Andreassen, Åshild; Soleng, Arnulf; Vene, Sirkka; Dudman, Susanne G.
Abstract Background: Tick-borne encephalitis (TBE) is an emerging tick-borne disease in Europe. In Norway, the first TBE case occurred in 1997, and since then 1–14 cases have been detected annually along the southern coast. No TBE cases have yet been notified from the eastern coastal area. This study was conducted to assess the need for diagnostic tests and vaccine recommendation for this part of Norway. Methods: Four hundred and sixty-one blood donors living in the county of Østfold were enrolled. After informed consent was obtained, the participants submitted a blood sample and filled out a questionnaire regarding tick bites, outdoor activities, and Flavivirus vaccines and diseases. Ixodes ricinus ticks were collected from the immediate vicinity and were examined in pools of 10 for TBE virus. Results: Eight human samples were TBE virus IgG-positive by ELISA and 5 of these samples were confirmed positive by neutralization test. Excluding the 2 samples from participants who had reported previous TBE vaccination, this shows a seroprevalence among blood donors of 0.65%. The existence of TBEV in the region was verified in nymphs of Ixodes ricinus by a prevalence of 0.14%. Conclusions: The seroprevalence of TBE virus IgG and the TBE virus detected in ticks, indicate that TBE cases could occasionally occur in the area. The results should be made available to health care personnel to raise awareness for preventative measures.